Activation of STAT3 integrates common profibrotic pathways to promote fibroblast activation and tissue fibrosis. Issue 1 (December 2017) - Chakraborty, Debomita; Šumová, Barbora; Mallano, Tatjana; Chen, Chih-Wei; Distler, Alfiya; Bergmann, Christina; Ludolph, Ingo; Horch, Raymund; Gelse, Kolja; Ramming, Andreas; Distler, Oliver; Schett, Georg; et al.
Abstract Signal transducer and activator of transcription 3 (STAT3) is phosphorylated by various kinases, several of which have been implicated in aberrant fibroblast activation in fibrotic diseases including systemic sclerosis (SSc). Here we show that profibrotic signals converge on STAT3 and that STAT3 may be an important molecular checkpoint for tissue fibrosis. STAT3 signaling is hyperactivated in SSc in a TGFβ-dependent manner. Expression profiling and functional studies in vitro and in vivo demonstrate that STAT3 activation is mediated by the combined action of JAK, SRC, c-ABL, and JNK kinases. STAT3-deficient fibroblasts are less sensitive to the pro-fibrotic effects of TGFβ. Fibroblast-specific knockout of STAT3, or its pharmacological inhibition, ameliorate skin fibrosis in experimental mouse models. STAT3 thus integrates several profibrotic signals and might be a core mediator of fibrosis. Considering that several STAT3 inhibitors are currently tested in clinical trials, STAT3 might be a candidate for molecular targeted therapies of SSc. STAT3 is a transcription factor that is activated in fibrotic diseases such as systemic sclerosis. Here the authors show that STAT3 is the converging point for multiple pro-fibrotic signalling pathways, and that its genetic ablation or inhibition ameliorate skin fibrosis in mouse models.